IMPLEMENTASI SOFTWARE AXATA POS DALAM MEMENUHI KEBUTUHAN SISTEM INFORMASI AKUNTANSI PADA KLINIK KESEHATAN DITINJAU DARI PERSPEKTIF MANAJEMEN BISNIS SYARIAH - Bagas Noval Pradipta; Lantip Susilowati; Husnul Haq (IAIN Batusangkar, 2020)
Health is one of the important things in life. Health service is the most important necessary, along with increasing public awareness of the importance of health. Sima Husada Clinic is a health clinic which is focused on outpatients and inpatients, in which the data processing transaction used is a manual system. In this research, the researcher will elaborate in outline about accounting information by using software AxataPOS. The aim of this research is to describe accounting program facilitiy, in order to simplify entering data transaction and organizing financial report. The research method of this study were descriptive research. In collecting the data, the researcher used observation directly about daily transaction, beside that the researcher also did interview with the manager and Administration. The result of this research showed that the implementation of software AxataPOS to Sima Husada Clinic can be applied since it eases the clinic in processing the data of financial transaction for instance recording the cash out and cash in, payroll, medical stock such as the outcoming item, the incoming item and stock opname, and in the perspective of sharia business management a system is very much needed to make it easier to achieve the benefit of society. In this case, automatically it will generate the financial report which is needed without a long stage.